2021
DOI: 10.1126/sciadv.abj7917
|View full text |Cite
|
Sign up to set email alerts
|

Frizzled BRET sensors based on bioorthogonal labeling of unnatural amino acids reveal WNT-induced dynamics of the cysteine-rich domain

Abstract: WNTs induce conformational changes in the extracellular CRD of Frizzleds irrespective of their signaling profile.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 72 publications
2
12
0
Order By: Relevance
“…Further work in this direction is required to clarify mechanistic details. Nevertheless, the emerging concept of conformational dynamics of FZDs is in agreement with general concepts of GPCR activation ( 42 ) and is further supported by previously reported WNT-induced dissociation of FZD dimers ( 43 ), WNT-induced changes in FRET-based FZD conformational sensors ( 20 , 38 ), WNT concentration-response curves for fluorescence changes in circularly permuted GFP (cpGFP)–tagged FZD conformational sensors ( 3 ), and the WNT-induced dynamics of the CRD of FZDs that precede alterations in core conformation ( 44 ). Thus, WNT-induced pathway selection and signal initiation of FZDs are not only determined by their proximity to different coreceptors but also appear to be, at least in part, determined by a conformational selection of WNT-FZD-DVL interaction.…”
Section: Discussionsupporting
confidence: 88%
“…Further work in this direction is required to clarify mechanistic details. Nevertheless, the emerging concept of conformational dynamics of FZDs is in agreement with general concepts of GPCR activation ( 42 ) and is further supported by previously reported WNT-induced dissociation of FZD dimers ( 43 ), WNT-induced changes in FRET-based FZD conformational sensors ( 20 , 38 ), WNT concentration-response curves for fluorescence changes in circularly permuted GFP (cpGFP)–tagged FZD conformational sensors ( 3 ), and the WNT-induced dynamics of the CRD of FZDs that precede alterations in core conformation ( 44 ). Thus, WNT-induced pathway selection and signal initiation of FZDs are not only determined by their proximity to different coreceptors but also appear to be, at least in part, determined by a conformational selection of WNT-FZD-DVL interaction.…”
Section: Discussionsupporting
confidence: 88%
“…We tested this model and concluded that WNTs induce FZD-DVL conformational dynamics independently of LRP5/6, clearly suggesting that (i) WNT-FZD interactions can occur independently of LRP5/6, that (ii) agonist-induced FZD-DVL dynamics potentially precede LRP5/6 signalosome formation and that (iii) WNT-induced conformational changes of FZDs regulate the initial communication with DVL in a receptor complex reminiscent of the ternary complex described for agonist- and effector-bound GPCRs ( 4, 22 ). The emerging concept of conformational dynamics of FZDs is in agreement with general concepts of GPCR activation ( 41 ) and is further supported by previously reported WNT concentration response curves for fluorescence changes in cpGFP-tagged FZD conformational sensors ( 3 ) and the WNT-induced dynamics of the cysteine-rich domain of FZDs that precede alterations in core conformation ( 42 ). Thus, WNT-induced pathway selection and signal initiation of FZDs is not only determined by their proximity to different co-receptors but appears to be – at least in part – determined by a conformational selection of WNT-FZD-DVL interaction.…”
Section: Discussionsupporting
confidence: 78%
“…Ye et al first employed the strategy for studies of GPCRs ( Ye et al, 2008 ). Specific unnatural amino acids can be introduced to facilitate “targeted photo-crosslinking” or bio-orthogonal covalent labeling with small-molecule fluorophores to create FRET or BRET conformational sensors ( Koole et al, 2017 ; Kowalski-Jahn et al, 2021 ). Simms and colleagues employed a targeted photo-cross-linking strategy to study the ECL2 of CALCRL and identified two major contact points for CGRP, I284 and L291 ( Simms et al, 2018 ).…”
Section: Molecular Characterization Of Gpcr–ramp Interactionsmentioning
confidence: 99%